Sex differences and pathology status correlated to the toxicity of some common carcinogens in experimental skin carcinoma. (September 2016) - Dehelean, Cristina A.; Soica, Codruta; Pinzaru, Iulia; Coricovac, Dorina; Danciu, Corina; Pavel, Ioana; Borcan, Florin; Spandidos, Demetrios A.; Tsatsakis, Aristidis M.; Baderca, Flavia
Abstract: The increased susceptibility of men as compared to women to develop different types of cancer, including skin cancer, is well known; however, the mechanisms involved in this process are still a matter of debate. This study aimed to obtain animal models of photo-chemically-induced skin carcinogenesis by exposure to ultraviolet radiation B (UVB) coupled with topical applications of a tumor initiator (7, 12-dimethylbenz( a )anthracene, DMBA) and a tumor promoter (12-O-tetradecanoylphorbol-13-acetate, TPA) in order to characterize the gender disparities regarding the skin lesions developed by the female and male SKH-1 hairless mice included in this study. Histopathological analysis confirmed the presence of malignant lesions in both cases, in female and male mice, following chronic exposure (24 weeks) to the noxious effects of the carcinogens applied, whereas the tumors in male mice had a more severe histological grade. In addition, tumor incidence, size and multiplicity were higher in male mice than in female mice. Graphical abstract: Highlights: Thorough study of the gender differences exhibited by skin cancer. New details concerning the pathology of chemically-induced skin cancer. Contribution to the toxicity evaluation of the chemical promoters used in experimental skin cancer. Histopathological evaluation of the changes at skin level during the evolution of skin cancer. Analysis of the pathological evolution in skin cancer as a result of its potentiation following UVB application.